Turkish national consensus on breast cancer management during temporary state of emergency due to COVID-19 outbreak - Sezer, Atakan (Turk J Surg, 2020)
OBJECTIVES: Cancer care is excessively influenced by the COVID-19 outbreak for various reasons. One of the major concerns is the tendency for delayed surgical treatment of breast cancer patients. The outbreak has urged clinicians to find alternative treatments until surgery is deemed to be feasible and safe. Here in this paper, we report the results of a consensus procedure which aimed to provide an expert opinion-led guideline for breast cancer management during the COVID-19 outbreak in Turkey. MATERIAL AND METHODS: We used the Delphi method with a 9-scale Likert scale on two rounds of voting from 51 experienced surgeons and medical oncologists who had the necessary skills and experience in breast cancer management. Voting was done electronically in which a questionnaire-formatted form was used. RESULTS: Overall, 46 statements on 28 different case scenarios were voted. In the first round, 37 statements reached a consensus as either endorsement or rejection, nine were put into voting in the second round since they did not reach the necessary decision threshold. At the end of two rounds, for 14 cases scenarios, a statement was endorsed as a recommendation for each. Thirty-two statements for the remaining 14 were rejected. CONCLUSION: There was a general consensus for administering neoadjuvant systemic therapy in patients with node-negative, small-size triple negative, HER2-positive and luminal A-like tumors until conditions are improved for due surgical treatment. Panelists also reached a consensus to extend the systemic treatment for patients with HER2-positive and luminal B-like tumors who had clinical complete response after neoadjuvant systemic therapy.